Involvement and regulation of the left anterior cingulate cortex in the ultrasonic communication deficits of autistic mice - Hou, Yilin; Li, Yuqian; Yang, Dingding; Zhao, Youyi; Feng, Tingwei; Zheng, Wei’an; Xian, Panpan; Liu, Xufeng; Wu, Shengxi; Wang, Yazhou (Frontiers in Behavioral Neuroscience, 2024)
Introduction Autism spectrum disorder (ASD) is a group of diseases often characterized by poor sociability and challenges in social communication. The anterior cingulate cortex (ACC) is a core brain region for social function. Whether it contributes to the defects of social communication in ASD and whether it could be physiologically modulated to improve social communication have been poorly investigated. This study is aimed at addressing these questions. Methods Fragile X mental retardation 1 (FMR1) mutant and valproic acid (VPA)-induced ASD mice were used. Male–female social interaction was adopted to elicit ultrasonic vocalization (USV). Immunohistochemistry was used to evaluate USV-activated neurons. Optogenetic and precise target transcranial magnetic stimulation (TMS) were utilized to modulate anterior cingulate cortex (ACC) neuronal activity. Results In wild-type (WT) mice, USV elicited rapid expression of c-Fos in the excitatory neurons of the left but not the right ACC. Optogenetic inhibition of the left ACC neurons in WT mice effectively suppressed social-induced USV. In FMR1−/−- and VPA-induced ASD mice, significantly fewer c-Fos/CaMKII-positive neurons were observed in the left ACC following USV compared to the control. Optogenetic activation of the left ACC neurons in FMR1−/− or VPA-pretreated mice significantly increased social activity elicited by USV. Furthermore, precisely stimulating neuronal activity in the left ACC, but not the right ACC, by repeated TMS effectively rescued the USV emission in these ASD mice. Discussion The excitatory neurons in the left ACC are responsive to socially elicited USV. Their silence mediates the deficiency of social communication in FMR1−/− and VPA-induced ASD mice. Precisely modulating the left ACC neuronal activity by repeated TMS can promote the social communication in FMR1−/− and VPA-pretreated mice.